The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ssresearch.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Status, emotional displays, and the relationally-based evaluation of criminals and their behavior

Abstract: This research uses status characteristics theory to expand our knowledge of the effects of status variables (e.g., race, education) and emotional displays on the antecedents of sentencingevaluations of offender dangerousness and offense seriousness. We present a theoretical formulation that combines three areas of status characteristics research -reward expectations, individual evaluative settings and valued personal characteristics. The result is a quantitative measure that aggregates relative differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 104 publications
1
26
1
Order By: Relevance
“…Although there has been much empirical support for the processes and assumptions outlined in RET in both collective task (Fisek & Hysom, 2004;Hogue & Yoder, 2003;Wagner, 1995Wagner, , 2000 and evaluative settings (Dilks et al, 2015;Fisek & Hysom, 2008;Hysom & Fisek, 2011;Melamed, 2011) we argue that in its current form RET may be too constraining for two reasons. First, the current operationalization of rewards includes only positive goal objects such as money, titles, and medals.…”
Section: Extending Ret: Allocations Of Negative Rewards Via Status Cuesmentioning
confidence: 77%
See 4 more Smart Citations
“…Although there has been much empirical support for the processes and assumptions outlined in RET in both collective task (Fisek & Hysom, 2004;Hogue & Yoder, 2003;Wagner, 1995Wagner, , 2000 and evaluative settings (Dilks et al, 2015;Fisek & Hysom, 2008;Hysom & Fisek, 2011;Melamed, 2011) we argue that in its current form RET may be too constraining for two reasons. First, the current operationalization of rewards includes only positive goal objects such as money, titles, and medals.…”
Section: Extending Ret: Allocations Of Negative Rewards Via Status Cuesmentioning
confidence: 77%
“…However, recent EST research has found that status generalization processes can occur in any evaluative setting that creates pressures for individuals to assess expectations in a relative manner (Erickson 1998). Several RET studies take place in these settings and empirically support the main assumptions of the theory (Dilks et al, 2015;Fisek & Hysom, 2008;Hysom & Fisek, 2011;Melamed, 2011).…”
Section: Status Characteristics Provide Information About Reward Expementioning
confidence: 90%
See 3 more Smart Citations